Bi-Hemispheric Engagement in the Retrieval of Autobiographical Episodes - Marie M. P. Vandekerckhove; Hans J. Markowitsch; Markus Mertens; Friedrich G. Woermann (Behavioural Neurology)
Functional magnetic resonance imaging (fMRI) was used to study the neural correlates of neutral, stressful, negative and positive autobiographical memories. The brain activity produced by these different kinds of episodic memory did not differ significantly, but a common pattern of activation for different kinds of autobiographical memory was revealed that included (1) largely bilateral portions of the medial and superior temporal lobes, hippocampus and parahippocampus, (2) portions of the ventral, medial, superior and dorsolateral prefrontal cortex, (3) the anterior and posterior cingulate, including the retrosplenial, cortex, (4) the parietal cortex, and (5) portions of the cerebellum. The brain regions that were mainly activated constituted an interactive network of temporal and prefrontal areas associated with structures of the extended limbic system. The main bilateral activations with left-sided preponderance probably reflected reactivation of complex semantic and episodic self-related information representations that included previously experienced contexts. In conclusion, the earlier view of a strict left versus right prefrontal laterality in the retrieval of semantic as opposed to episodic autobiographical memory, may have to be modified by considering contextual variables such as task demands and subject variables. Consequently, autobiographical memory integration should be viewed as based on distributed bi-hemispheric neural networks supporting multi-modal, emotionally coloured components of personal episodes.